TEACHING INTERCULTURAL COMPETENCE: APPROACHES, METHODS AND TECHNIQUES (KONFERENSIYA, 2026)
• The current article deals with the approaches, methods and techniques which require individual information about a particular culture, besides the presence of skills empathy, tolerance, reflection. There are definitions of intercultural competence, where key positions are focused on the ability phenomenon. Translators help people overcome languages barriers, dispel their suspicion and serve as a bridge in intercultural communication. Listening, observing, evaluating: using patience and perseverance to identify and minimize ethnocentrism, seek out cultural clues and meaning• Analyzing, interpreting and relating: seeking out linkages, causality and relationships using comparative techniques of analysis• Critical thinking: viewing and interpreting the world from other cultures’ point of view and identifying one’s own.